Leishmania infantum Seroprevalence in Cats From Touristic Areas of Italy and Greece - Morelli, Simone; Colombo, Mariasole; Dimzas, Dimitris; Barlaam, Alessandra; Traversa, Donato; Di Cesare, Angela; Russi, Ilaria; Spoletini, Roberta; Paoletti, Barbara; Diakou, Anastasia (Frontiers in Veterinary Science, 2020)
Leishmaniosis by Leishmania infantum is a major zoonotic Vector-Borne Disease (VBD) in terms of geographic distribution, pathogenicity and zoonotic potential. While dogs are the main reservoir of L. infantum, the infection in cats is poorly understood although increasingly reported from enzootic and non-enzootic areas. The Mediterranean basin is a key area for leishmaniosis and includes touristic spots that require continuous surveillance for VBDs in consideration of the growing tendency of tourists to travel with their pets. This study evaluated L. infantum seroprevalence in cats living in selected touristic localities of Italy and Greece. A total of 269 cat serum samples from three Sites i.e., 76, 40, and 153 from Adriatic Coast of Abruzzo, Italy (Site A), Giglio Island, Tuscany, Italy (Site B), and Mykonos Island, Greece (Site C), respectively, were included in the survey. Sera samples were subjected to an indirect immunofluorescence antibody assay for the detection of anti-L. infantum specific IgG. Associations between possible risk factors and seropositivity to L. infantum were statistically evaluated. Antibodies against L. infantum were detected in eight out of 269 (3.0%) cats tested i.e., 4/76 (5.3%), 1/40 (2.5%), and 3/153 (2.0%), from sites A, B, and C, respectively. A statistical association between anti-L. infantum antibodies and cohabitation with dogs was shown. This study indicates that feline populations living in the examined Italian and Greek touristic areas are exposed to L. infantum and that they may contribute to the circulation of L. infantum, enhancing the risk of infection for dogs and humans.